Software Engineering Approaches for Building Intelligent Systems in Public Service and Community Development - Popal; Rastagari, Mohammad Aziz; Jawad Danish; Hamzah Alaidaros (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The growing integration of intelligent systems in public services and community development highlights the need for robust software engineering approaches. This study systematically reviews literature published between 2018 and 2025 to examine the design, implementation, and ethical integration of intelligent systems in public sector contexts. Using databases such as IEEE Xplore, ScienceDirect, SpringerLink, Emerald Insight, and MDPI, 230 records were initially identified, with 20 peer-reviewed articles meeting the inclusion criteria. Findings reveal that requirements engineering, agile development, and model-driven design are effective in creating adaptive, scalable, and citizen-centric systems. Ethical and accountability considerations, participatory design, and governance frameworks are essential to foster trust and inclusivity. Challenges such as infrastructure limitations, workforce gaps, and technical barriers were noted, alongside opportunities for enhanced efficiency, automation, and citizen engagement. Overall, integrating technical rigor with ethical and participatory practices ensures the successful adoption of intelligent systems in public services.